Diagnóstico do estado geoambiental da área urbana do município de Cubatão (SP) / Geoenvironmental conditions diagnosis of the urban area of Cubatão, São Paulo, Brazil - Leandro de Godoi Pinton; Cenira Maria Lupinacci da Cunha (Sociedade & Natureza)
The degradation of landscapes which involves the urban area of Cubatão city (SP) is derived from spatial organizations outlined sócio-economic transformations over the last centuries, especially by an urbanization model established since the second half of the 20th century. In such context, obtaining data on regulating capacity of the landscapes’ geocological functions according to the anthropic intervention degree in its natural components constitutes as an aid instrument to the environmental planning. Thus, this study aimed to discuss the geoenvironmental conditions diagnosis of the landscapes from the urban area of Cubatão city (SP), carried out through the methodology proposed by Geoecology on scale of 1:10.000. The research was supported by the methodological principles of the General Systems Theory. The analysis of the diagnosis, developed from the assessment of data represented in particular cartographic document, allowed the identification of environmental problems related to the breach of environmental regulations and rupture of use potencial capacity of the studied area landscapes.